Techno-economic performance modelling of bifacial and tracking PV systems worldwide - Rodriguez-Gallegos, Carlos D.; Liu, Haohui; Gandhi, Oktoviano; Singh, Jai Prakash; Krishnamurthy, Vijay; Kumar, Abhishek; Stein, Joshua S.; Li, Li; Wang, Shitao; Reindl, Thomas; Peters, Ian Marius (Conference Record of the IEEE Photovoltaic Specialists Conference, 2021)
Todays commercial and utility photovoltaic (PV) installations predominantly use monofacial PV-modules in a mounting structure with a fixed-tilt. In recent years, front and rear efficiencies of bifacial PV modules have improved and their cost has dropped, as has the cost for single-axis and dual-axis trackers. These advances make those two technologies interesting options to improve the yield of PV installations. In this work, we present a comparison of the calculated techno-economic performance of conventional installations and different combinations of bifacial and tracking configurations. We find that installations with bifacial modules and one-axis trackers provide the greatest techno-economic benefit over monofacial fixed-tilt installation by increasing yield by, on average 35%, and reducing LCOE on the vast majority of locations in the world by more than 10%. Dual axis trackers achieve even higher yields, yet the high cost for these trackers results in an overall higher LCOE. Sensitivity analyses reveal that our conclusions are robust in general, but the best configuration in a given location still requires analyzing local conditions in detail.
CRIS-Team Scopus Importer:2022-06-05
Keywords: bifacial modules; bifacial tracking; dual axis trackers; energy yield; levelized cost of electricity; monofacial modules; photovoltaic systems; single axis trackers